Calibrating Students’ Performance in Mathematics: A Rasch Model Analysis - Shamsuddin, Hasni; Abdul Razak, Nordin; Zamri Khairani, Ahmad (International Journal of Engineering and Technology, 2018)
Rasch model analysis is an important tools in analysing students’ performance at item level. As such, the purpose of this study is to calibrate 14 years old students’ performance in mathematics test based on the item difficulty parameter. 307 Form 2 students provide responses for this study. A 40-item multiple choice test was developed to gauge the responses. Results show that two of the items need to be dropped since they did not meet the Rasch model’s expectations. Analysis on the remaining items showed that the students were most competent in item related to Directed Numbers (mean = -1.445 logits), while they are least competent in the topic of Circle (mean = 1.065 logits). We also provide calibration of the performance at item level. In addition, we discuss how to the findings might be helpful for teachers in addressing students’ difficulty in the topics.